1989
DOI: 10.3109/01460868909038035
|View full text |Cite
|
Sign up to set email alerts
|

Home Parenteral Nutrition for the Child with Cancer

Abstract: Compliance with treatment is greatly increased when the caregiver(s) understand the treatment, the need for the treatment, and the need for strict adherence to sterile technique. When the caregiver is not ready to handle home care of the child, compliance is less than optimal and may be a threat to the child. Parenteral nutrition support can be both safe and effective in children with cancer when the family and health-care team work together. Nutrition support facilitates treatment of the whole child and can h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The remaining 30 studies from the search and the 3 studies identified in the reference lists were reviewed in full and assessed for inclusion. Twenty‐eight 6, 8, 20–27, 30–47 of the 33 studies did not meet the inclusion criteria (Table I), leaving 5 studies relevant to the final review (Table II). The number of participants in the included studies ranged from 14 to 45.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 30 studies from the search and the 3 studies identified in the reference lists were reviewed in full and assessed for inclusion. Twenty‐eight 6, 8, 20–27, 30–47 of the 33 studies did not meet the inclusion criteria (Table I), leaving 5 studies relevant to the final review (Table II). The number of participants in the included studies ranged from 14 to 45.…”
Section: Resultsmentioning
confidence: 99%
“…Research on home treatment for children with cancer has focused primarily on administration of intravenous antibiotics and palliative care (Bendorf & Meehan 1989, Chambers et al . 1989, Wiernikowski et al .…”
Section: Introductionmentioning
confidence: 99%